2017
DOI: 10.5194/bg-2017-224
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ocean acidification changes the structure of an Antarctic coastal protistan community

Abstract: <p><strong>Abstract.</strong> Antarctic near-shore waters are amongst of the most vulnerable in the world to ocean acidification. Microbes occupying these waters are critical drivers of ecosystem productivity, elemental cycling and ocean biogeochemistry, yet little is known about their sensitivity to ocean acidification. An unreplicated, six-level dose-response experiment was conducted using 650 L incubation tanks (minicosms) adjusted to fugacity of carbo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…9a), it was possible that this response was driven by a decline in grazing by heterotrophs Westwood et al, 2018) instead of a direct CO 2 -related promotion of bacterial growth. The subsequent decline in abundance was likely due to topdown control from the heterotrophic nanoflagellate community, which displayed an increase in abundance at this time (Hancock et al, 2017). Bacterial tolerance to high CO 2 has been reported previously in this region Westwood et al, 2018) and has also been reported in numerous studies in the Arctic (Grossart et al, 2006;Allgaier et al, 2008;Paulino et al, 2008;Baragi et al, 2015;Wang et al, 2016), suggesting that the marine bacterial community will be resilient to increasing CO 2 .…”
Section: Ocean Acidification Effects On Bacterial Productivitymentioning
confidence: 77%
See 4 more Smart Citations
“…9a), it was possible that this response was driven by a decline in grazing by heterotrophs Westwood et al, 2018) instead of a direct CO 2 -related promotion of bacterial growth. The subsequent decline in abundance was likely due to topdown control from the heterotrophic nanoflagellate community, which displayed an increase in abundance at this time (Hancock et al, 2017). Bacterial tolerance to high CO 2 has been reported previously in this region Westwood et al, 2018) and has also been reported in numerous studies in the Arctic (Grossart et al, 2006;Allgaier et al, 2008;Paulino et al, 2008;Baragi et al, 2015;Wang et al, 2016), suggesting that the marine bacterial community will be resilient to increasing CO 2 .…”
Section: Ocean Acidification Effects On Bacterial Productivitymentioning
confidence: 77%
“…Numerous photophysiological investigations on individual phytoplankton species also report species-specific tolerances to increased CO 2 (Gao et al, 2012a;Gao and Campbell, 2014;Trimborn et al, 2013Trimborn et al, , 2014, and a general trend toward smaller-celled communities with increased CO 2 has been reported in ocean acidification studies globally . Changes in community structure were observed with increasing CO 2 , with taxon-specific thresholds of CO 2 tolerance (Hancock et al, 2017). Within the diatom community, the response was also related to size, leading to an increase in abundance of small (< 20 µm) diatoms in the higher CO 2 treatments (≥ 953 µatm).…”
Section: Ocean Acidification Effects On Phytoplankton Productivitymentioning
confidence: 82%
See 3 more Smart Citations